Transformational Leadership as a Driver of International Accreditation: A Strategic Management Model for Private Higher Education - Lativa Salsabila; Achadi Budi Santosa; Muhammad Zuhaery (Al-Qalam Institue, 2026)
This study investigates the transformational leadership model employed by faculty deans in driving international accreditation achievement within private higher education. Employing a qualitative case study design with purposive sampling, data were collected through in-depth semi-structured interviews with nine participants—a dean, five lecturers, and four students—and analyzed using systematic thematic analysis supported by ATLAS.ti software. The analysis identified three overarching themes that form a seven-dimensional, three-layer leadership model extending Bass and Riggio's (2006) framework by integrating foundational value dimensions with operational-contextual and impact dimensions: Idealized Influence as the foundation of institutional trust; Inspirational Motivation and Intellectual Stimulation as drivers of collective commitment; and Individualized Consideration and Strategic Leadership as mechanisms for sustainable institutional development. This model facilitated the international accreditation of three study programs, nearly doubled student enrollment, and measurably improved faculty performance. The findings offer a theoretically grounded and empirically validated reference for higher education leaders pursuing institutional internationalization.